2017
DOI: 10.1103/physrevb.96.054409
|View full text |Cite
|
Sign up to set email alerts
|

Spin-mechanical inertia in antiferromagnets

Abstract: Angular momentum conservation has served as a guiding principle in the interplay between spin dynamics and mechanical rotations. However, in an antiferromagnet with vanishing magnetization, new fundamental rules are required to properly describe spin-mechanical phenomena. Here we show that the Néel order dynamics affects the mechanical motion of a rigid body by modifying its inertia tensor in the presence of strong magnetocrystalline anisotropy. This effect depends on temperature when magnon excitations are co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
(26 reference statements)
0
4
0
1
Order By: Relevance
“…Temperature dependence of the fieldlike SOT is different in as-grown Pt/Co and annealed Pt/CoFeB bilayers [71]. The unexpected temperature dependence of the fieldlike SOT suggests that processes involving phonons or magnons may play an important role [1,72].…”
Section: Arxiv:181011003v2 [Cond-matmtrl-sci] 5 Feb 2019mentioning
confidence: 99%
“…Temperature dependence of the fieldlike SOT is different in as-grown Pt/Co and annealed Pt/CoFeB bilayers [71]. The unexpected temperature dependence of the fieldlike SOT suggests that processes involving phonons or magnons may play an important role [1,72].…”
Section: Arxiv:181011003v2 [Cond-matmtrl-sci] 5 Feb 2019mentioning
confidence: 99%
“…随着研究的深入, 关注点还是集中在超快磁化 强度翻转. 在反铁磁体中自旋之间的交换相互作用 导致了一种惯性行为 [11,59,60] , 数值模拟表明它极大 影响了反铁磁体中的自旋翻转. 虽然在光学 [61,62] 上产生的100 fs强磁场脉冲的作用过程中, 自旋方 向几乎没有变化, 但该脉冲传递足够的自旋系统的 动量, 以克服势垒, 在此作用后很长时间内重新定 向到一个新的亚稳态.…”
Section: 惯性效应驱动的磁化强度的翻转unclassified
“…Detection of magnon-mediated spin signals from AFM insulators, typically measured through the inverse spin Hall effect, has also matured to the point of experimental implementation. [6][7][8] It has been shown that AFM spin waves possess pointed dynamical distinctions from their ferromagnetic (FM) counterpart, [9][10][11] especially in the presence of spin texture [12][13][14][15][16][17] or broken inversion symmetry. 11,12,18,19 In particular, collinear AFMs possess two degenerate spin wave eigenmodes of opposite chirality.…”
Section: Introductionmentioning
confidence: 99%
“…There is very little "quantum" about it in our case, but the nomenclature is already out there. 10,[88][89][90] Appendix C: A monolithic substitution for introducing the spin wave fields…”
mentioning
confidence: 99%